Challenges and Opportunities of Therapies Targeting Early Life Immunity for Pediatric HIV Cure - Berendam, Stella J.; Nelson, Ashley N.; Yagnik, Bhrugu; Goswami, Ria; Styles, Tiffany M.; Neja, Margaret A.; Phan, Caroline T.; Dankwa, Sedem; Byrd, Alliyah U.; Garrido, Carolina; Amara, Rama R.; Chahroudi, Ann; et al. (Frontiers in Immunology, 2022)
Early initiation of antiretroviral therapy (ART) significantly improves clinical outcomes and reduces mortality of infants/children living with HIV. However, the ability of infected cells to establish latent viral reservoirs shortly after infection and to persist during long-term ART remains a major barrier to cure. In addition, while early ART treatment of infants living with HIV can limit the size of the virus reservoir, it can also blunt HIV-specific immune responses and does not mediate clearance of latently infected viral reservoirs. Thus, adjunctive immune-based therapies that are geared towards limiting the establishment of the virus reservoir and/or mediating the clearance of persistent reservoirs are of interest for their potential to achieve viral remission in the setting of pediatric HIV. Because of the differences between the early life and adult immune systems, these interventions may need to be tailored to the pediatric settings. Understanding the attributes and specificities of the early life immune milieu that are likely to impact the virus reservoir is important to guide the development of pediatric-specific immune-based interventions towards viral remission and cure. In this review, we compare the immune profiles of pediatric and adult HIV elite controllers, discuss the characteristics of cellular and anatomic HIV reservoirs in pediatric populations, and highlight the potential values of current cure strategies using immune-based therapies for long-term viral remission in the absence of ART in children living with HIV.